Employee Conflict Management in Government Organization - Somkliang, Aurai; Kongrungchok, Arus; Nakphin, Siyathorn (Hatyai Academic Journal, 2020)
This article is concerned with employee conflict management in governmental organizations in order to analyze and synthesize the causes and approaches to conflict management occurring in governmental organizations based on concepts and theories related to conflict management. Related literature was collected and reviewed, and became tools to analyze the contents of the occurred conflict cases and management. In summary, the concepts and recommendations approached through meanings, concepts, theories, causes, types, and management of the conflict in the governmental organizations. The result discovered that conflict was inevitable and there were six causes of conflicts in the governmental organizations consisting of different goals, resource competition, defective communication and error information, differences of opinion and working standards, incoherent organizational structures, and popularity conflicts. There were also five methods of conflict management in governmental organizations: competition or subjugation, cooperation, avoidance, acceptance, and compromise. Furthermore, the most significant point which creatively led to the success of the conflict management depended on their leader’s understanding of the nature of the conflict and the leader’s open-mindedness in accepting all opinions from the employees within the organizations in order to be a starting point of the sustainable solution for internal problems within the organizations.